Arc Length of ln ( x ) \ln\left(x\right)

Calculus Level 5

Let f ( n ) f(n) denote the arc length of the curve y = ln ( x ) y=\ln\left(x\right) in the interval x [ 1 , n ] x\in\left [1,n\right ] . Find lim n ( n f ( n ) ) . \lim_{n\to\infty}\big(n-f(n)\big). If your answer is of the form ln ( a b ) + c d \ln\left(\sqrt{a}-b\right)+\sqrt{c}-d , where a a , b b , c c , and d d are non-negative integers and a a and c c are not perfect squares, find a + b + c + d a+b+c+d .

4 4 5 5 6 6 7 7 8 8 None of the above

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Joseph Newton
Jun 11, 2018

Arc length = a b 1 + ( d y d x ) 2 d x f ( n ) = 1 n 1 + ( d d x ln x ) 2 d x = 1 n 1 + ( 1 x ) 2 d x = 1 n 1 x x 2 + 1 d x let x = tan θ , d x = sec 2 θ d θ f ( n ) = tan 1 ( 1 ) tan 1 ( n ) sec 2 θ tan θ tan 2 θ + 1 d θ = π 4 tan 1 ( n ) sec 2 θ sin θ sec θ sec 2 θ d θ = π 4 tan 1 ( n ) sec 2 θ csc θ d θ = [ tan θ csc θ ] π 4 tan 1 ( n ) π 4 tan 1 ( n ) tan θ ( csc θ cot θ ) d θ = [ sec θ ] π 4 tan 1 ( n ) + π 4 tan 1 ( n ) csc θ d θ = sec tan 1 ( n ) sec π 4 [ ln ( csc θ + cot θ ) ] π 4 tan 1 ( n ) = 1 + n 2 2 ln [ csc tan 1 ( n ) + cot tan 1 ( n ) ] + ln ( csc π 4 + cot π 4 ) = 1 + n 2 2 ln ( 1 + n 2 n + 1 n ) + ln ( 2 + 1 ) Now, lim n ( n f ( n ) ) = lim n [ n 1 + n 2 + 2 + ln ( 1 + n 2 n 1 n ) ln ( 2 + 1 ) ] = lim n [ n 2 ( 1 + n 2 ) n + 1 + n 2 + 2 + ln ( 1 n 2 + 1 1 n ) + ln ( 1 2 + 1 ) ] = lim n [ 1 n + 1 + n 2 + ln ( 1 n 2 + 1 1 n ) + ln ( 2 1 2 1 ) + 2 ] = 0 + ln ( 0 + 1 0 ) + ln ( 2 1 2 1 ) + 2 = ln ( 1 ) + ln ( 2 1 ) + 2 = ln ( 2 1 ) + 2 \begin{aligned}\text{Arc length}&=\int_a^b\sqrt{1+\left(\frac{dy}{dx}\right)^2}dx\\ f(n)&=\int_1^n\sqrt{1+\left(\frac{d}{dx}\ln x\right)^2}dx\\ &=\int_1^n\sqrt{1+\left(\frac{1}{x}\right)^2}dx\\ &=\int_1^n \frac{1}{x}\sqrt{x^2+1}dx\\ \text{let }x=\tan\theta,&\quad\therefore dx=\sec^2\theta d\theta\\ f(n)&=\int_{\tan^{-1}(1)}^{\tan^{-1}(n)} \frac{\sec^2\theta}{\tan\theta}\sqrt{\tan^2\theta+1}d\theta\\ &=\int_\frac{\pi}{4}^{\tan^{-1}(n)} \frac{\sec^2\theta}{\sin\theta\sec\theta}\sqrt{\sec^2\theta}d\theta\\ &=\int_\frac{\pi}{4}^{\tan^{-1}(n)} \sec^2\theta\csc\theta d\theta\\ &=\left[\tan\theta\csc\theta\right]_\frac{\pi}{4}^{\tan^{-1}(n)}-\int_\frac{\pi}{4}^{\tan^{-1}(n)} \tan\theta(-\csc\theta\cot\theta) d\theta\\ &=\left[\sec\theta\right]_\frac{\pi}{4}^{\tan^{-1}(n)}+\int_\frac{\pi}{4}^{\tan^{-1}(n)} \csc\theta d\theta\\ &=\sec\tan^{-1}(n)-\sec\frac{\pi}{4}-\left[\ln(\csc\theta+\cot\theta)\right]_\frac{\pi}{4}^{\tan^{-1}(n)}\\ &=\sqrt{1+n^2}-\sqrt2-\ln\left[\csc\tan^{-1}(n)+\cot\tan^{-1}(n)\right]+\ln\left(\csc\frac{\pi}{4}+\cot\frac{\pi}{4}\right)\\ &=\sqrt{1+n^2}-\sqrt2-\ln\left(\frac{\sqrt{1+n^2}}{n}+\frac{1}{n}\right)+\ln\left(\sqrt2+1\right)\\ \text{Now, }\lim_{n\to\infty}\left(n-f(n)\right)&=\lim_{n\to\infty}\left[n-\sqrt{1+n^2}+\sqrt2+\ln\left(\frac{\sqrt{1+n^2}}{n}-\frac{1}{n}\right)-\ln\left(\sqrt2+1\right)\right]\\ &=\lim_{n\to\infty}\left[\frac{n^2-(1+n^2)}{n+\sqrt{1+n^2}}+\sqrt2+\ln\left(\sqrt{\frac{1}{n^2}+1}-\frac{1}{n}\right)+\ln\left(\frac{1}{\sqrt2+1}\right)\right]\\ &=\lim_{n\to\infty}\left[\frac{1}{n+\sqrt{1+n^2}}+\ln\left(\sqrt{\frac{1}{n^2}+1}-\frac{1}{n}\right)+\ln\left(\frac{\sqrt2-1}{2-1}\right)+\sqrt2\right]\\ &=0+\ln\left(\sqrt{0+1}-0\right)+\ln\left(\frac{\sqrt2-1}{2-1}\right)+\sqrt2\\ &=\ln(1)+\ln\left(\sqrt2-1\right)+\sqrt2\\ &=\ln\left(\sqrt2-1\right)+\sqrt2\end{aligned} So the answer is 2 + 1 + 2 + 0 = 5 2+1+2+0=\boxed{5}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...